(untitled) (Journal of the College of Basic Education, 2023)
This paper is presenting a model to make the dream of semantic web come true, it is just so far for the re-cent technology to completely move the whole internet Architecture to semantic Architecture, the model presented along this paper is to use personalization techniques to customize web servers in a way to make possessed web pages looks like it has been semantically composed. This model is a step toward a possible and meaningful synthesis of search engines and agent technology to participate in personalize customer needs and build semantic relations within the page content.